IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA PENDIDIKAN AGAMA ISLAM DI SMPN 25 SAMARINDA - Muhammad Nur (Nusantara Interdisciplinary Journal of Education Studies and Society (NIJESS), 2024)
Education in Indonesia cannot be separated from the curriculum, the curriculum will continue to develop all the time until now it has reached the independent learning curriculum, which is expected to be able to improve the quality of students in various fields, not only academic, but also non-academic. In terms of academics, students are not only required to think at a low level, but also at a high level, so that they have critical thinking skills, which continue to be developed. This research, with a qualitative approach and data collection techniques through interviews, observation and documentation, illustrates that collaboration This is not just an effort, but a serious step to advance the quality of religious education. The application of the independent curriculum becomes a reference for educators to be more creative and innovative. The results of the research highlight the implementation of the independent curriculum in Islamic religious education at SMPN 25 Samarinda in order to increase reference regarding the implementation of the independent curriculum